Calculation Study of Double Pipe Type Heat Exchanger in LNG Plant Pre-Design with Capacity 250 tons/hour - Novianarenti, Eky; Ningsih, Erlinda; Rahman, Nanik Astuti (Journal of Mechanical Engineering, Science, and Innovation, 2024)
In industrial processes, heat exchangers are very important tools and are always needed. Heat exchangers can be used to increase and decrease the temperature. The most widely used type of heat exchanger is the Double Pipe or DPHE type. The LNG plant is one of the industries that uses a heat exchanger in the process of lowering the initial temperature of the LNG to change the gas phase to liquid. The aim of this study is to obtain better efficiency in the LNG manufacturing process, so it is necessary to carry out a heat exchanger design study. Based on the design calculation results, it was found that Heat Exchanger type 2-4, material Carbon steel, area 2076, 16 m2, Rd 0.005 hr ft2 oF/btu and ΔP of 4.4051 psi. It can be concluded that the heat changer design is feasible to operate safely and without any obstacles.